2016
DOI: 10.1074/jbc.m116.726836
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific Gene Inactivation of the Transcription Factor ATF4 Alleviates Alcoholic Liver Steatosis in Mice

Abstract: Although numerous biological functions of the activating transcription factor 4 (ATF4) have been identified, a direct effect of ATF4 on alcoholic liver steatosis has not been described previously. The aim of our current study is to investigate the role of ATF4 in alcoholic liver steatosis and elucidate the underlying mechanisms. Here, we showed that the expression of ATF4 is induced by ethanol in hepatocytes in vitro and in vivo, and liverspecific ATF4 knock-out mice are resistant to ethanol-induced liver stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…In addition to cellular stress response genes, there was an upregulation of retinol binding protein 4 (rbp4) (P = 0.009, 1% EtOH), a circulating factor that regulates glucose and lipid metabolism, in both 0.5% and 1% EtOH adults ( Figure 7J, Supplemental Tables 13 and 16, refs. [55][56][57]. Additional significantly dysregulated genes included those critical for immune function (mhc1uba, P = 6.71 × 10 -11 , 1% EtOH), glycogen storage (gyg1a, P × 10 -07 , 1% EtOH), and iron homeostasis (fth1a, slc40a1, tfa, hamp) ( Figure 7J and Supplemental Tables 13 and 16).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cellular stress response genes, there was an upregulation of retinol binding protein 4 (rbp4) (P = 0.009, 1% EtOH), a circulating factor that regulates glucose and lipid metabolism, in both 0.5% and 1% EtOH adults ( Figure 7J, Supplemental Tables 13 and 16, refs. [55][56][57]. Additional significantly dysregulated genes included those critical for immune function (mhc1uba, P = 6.71 × 10 -11 , 1% EtOH), glycogen storage (gyg1a, P × 10 -07 , 1% EtOH), and iron homeostasis (fth1a, slc40a1, tfa, hamp) ( Figure 7J and Supplemental Tables 13 and 16).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ATF4 deficiency or ATF4 knockdown can also protect the liver from diet-induced and ethanol-induced steatosis in mice [44,46,56,57]. Expression of lipogenic enzyme-encoding genes and production of very low-density lipoprotein (VLDL)-triglyceride is reduced in the liver of ATF4-deficient mice [47].…”
Section: G6pase Pckmentioning
confidence: 99%
“…Several studies suggested that ISR activation contribute to pathogenesis of liver steatosis (LS). ATF4 has been shown to activate lipogenesis in hepatocytes (15)(16)(17) and increase the expression of hepatic very-low-density lipoprotein receptor, which contribute to worsened hepatic steatosis (HS). (18) In line with this, ISR inhibition by transgenic overexpression of GADD34 in the liver suppressed lipogenesis and protected mice from HS.…”
mentioning
confidence: 99%